2020
DOI: 10.1159/000508982
|View full text |Cite
|
Sign up to set email alerts
|

Ceramic-on-Ceramic Total Hip Arthroplasty with Large Diameter Heads: A Systematic Review

Abstract: Ceramic-on-ceramic (COC) total hip arthroplasties (THAs) with large heads (>36 mm) were introduced to reduce dislocation rates and restore the hip anatomy as closely as possible to the native one. To date, the literature is scarce and fragmented; a review is desirable to point out the outcomes and the possible specific complications (noise, groin pain, and taperosis). A systematic review about large-diameter COC THAs was conducted according to the PRISMA guidelines. The PubMed and Cochrane databases were searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…The wear resistance of acetabular Liner was always a key factor that we must consider for young patients. Though the volumetric wear rates of polyethylene lining were very low 0.022 mm/year, proving highly crosslinked polyethylene was durable in THAs [17] and hip abnormal noise was mainly appeared in ceramic-onceramic THAs [18], the advantages of 4th-COC were also obvious in our experience [19]. However, most research on Crowe II/III had few such detailed surgical date [14].…”
Section: Prothesismentioning
confidence: 61%
“…The wear resistance of acetabular Liner was always a key factor that we must consider for young patients. Though the volumetric wear rates of polyethylene lining were very low 0.022 mm/year, proving highly crosslinked polyethylene was durable in THAs [17] and hip abnormal noise was mainly appeared in ceramic-onceramic THAs [18], the advantages of 4th-COC were also obvious in our experience [19]. However, most research on Crowe II/III had few such detailed surgical date [14].…”
Section: Prothesismentioning
confidence: 61%
“…Last, a large femoral head with a diameter of 36 mm was used in almost all implants (98.3%). It has been shown that CoC bearings decrease the cumulative long‐term risk of dislocation compared with that for CoP bearings 38 , especially when implanted with a large‐diameter (≥32 mm) femoral head 39 , 40 . HO was seen in 12 (6.7%) of all postoperative hips.…”
Section: Discussionmentioning
confidence: 99%
“…The benefits of using LDH in the primary setting includes a reduction in the risk of impingement (allowing for a greater range of movement and a decreased risk of dislocation); improved abductor function and hip kinematics; and a reduced long-term risk of implant loosening. 56 Our study analysis functional outcomes for the use of LDH in the revision setting. This study demonstrates an improvement in functional outcomes when using LDH for revision surgery.…”
Section: Discussionmentioning
confidence: 99%